'The Game' that stopped two nations: Development and diplomacy in the case of the 2015 New Zealand All Black's and Manu Samoa rugby test match in Samoa. (4th May 2021) - Stewart‐Withers, Rochelle; Hapeta, Jeremy; Greener, Bethan
Abstract : This article investigates the impacts of the 2015 New Zealand (NZ) All Black rugby test match with Manu Samoa in Samoa: the 'Game that stopped two nations' (henceforth referred to as 'the Game'). Outlining key concepts as well as events and experiences surrounding the Game, this paper reflects on how the Game aligns with the Sustainable Development Goals as well as NZ's current Pacific Reset Agenda, an agenda which aims to increase understanding, friendship, mutual benefit, collective ambition and sustainability (Ministry of Foreign Affairs and Trade, 2017). A Likert‐styled questionnaire, a 15‐category ranking exercise, semi‐structured interviews, analysis of relevant media and other sources, informal discussions and participant observation help to provide insights into how sport for diplomacy and development functions. The Game was viewed as providing an opportunity for income generation, most participants felt excited to have shared in the experience, and many were hopeful as to what this might mean for future NZ/Samoan relations. However, we argue that, overall, this event represented a missed opportunity. If sport diplomacy events are to authentically contribute to diplomatic and development goals, more needs to be done to create meaningful and enduring engagement.